2016
DOI: 10.1021/acs.jpcb.5b12477
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl benzyl trimethylammonium chloride) Homo and Block Copolymers Complexation with DNA

Abstract: In this work we focus on the use of novel homo and block copolymers based on poly(vinyl benzyl trimethylammonium chloride) as gene delivery vectors. The homopolymers and block copolymers were synthesized by RAFT polymerization schemes and molecularly characterized. DNA/polymer complexes (polyplexes) in a wide range of N/P (amino-to-phosphate groups) ratios were prepared. The ability of the novel polymers to form complexes with linear DNA was investigated by light scattering, zeta potential, and ethidium bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 54 publications
4
57
0
Order By: Relevance
“…The polyplex particles were mostly spherical (Figure c,d), as observed earlier . Objects with morphology deviating from the spherical one (appearing in the TEM images as irregular circular objects) were only occasionally observed.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The polyplex particles were mostly spherical (Figure c,d), as observed earlier . Objects with morphology deviating from the spherical one (appearing in the TEM images as irregular circular objects) were only occasionally observed.…”
Section: Resultssupporting
confidence: 81%
“…Molecular characteristics and dispersity, determined by independent techniques (AF4, static light scattering, agarose gel electrophoresis), are presented in the Supporting Information. The synthesis of homopolymer PVBTMAC and block copolymer PVBTMAC–POEGMA was performed by reversible addition‐fragmentation chain transfer (RAFT) polymerization in aqueous media as described elsewhere . The chemical structures and molecular characteristics of the (co)polymer are presented in Scheme and Table , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its copolymers with polycations, such as polylysine, PEI, and poly(2‐(dimethylamino)ethyl methacrylate), have been investigated in depth. In recent years, another thermo‐responsive polymer, poly(oligoethyleneglycol methyl ether methacrylate) (POEGMA), a brush‐shaped derivative of PEG, has been commonly used in PEC micelles owing to its higher biocompatibility and easy synthesis using controlled polymerization techniques. LCST of POEGMA can be adjusted by altering PEG chain length or combining different OEGMA monomers having varying length PEG chains .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Recently, it has been suggested that novel homo and block copolymers based on poly(vinyl benzyl trimethylammonium chloride) may be used as gene delivery vectors. 14 The majority of the cationic polymers, bearing an amine function, can be protonated; the relative number of the protonable amines differs for each polymer. The resultant characteristics (size and size distribution, transfection efficiency, stability, toxicity etc.…”
Section: Introductionmentioning
confidence: 99%